Beyond Activated Carbon: Graphite‐Cathode‐Derived Li‐Ion Pseudocapacitors with High Energy and High Power Densities. Issue 14 (15th February 2019) - Wang, Gang; Oswald, Steffen; Löffler, Markus; Müllen, Klaus; Feng, Xinliang
Abstract: Supercapacitors have aroused considerable attention due to their high power capability, which enables charge storage/output in minutes or even seconds. However, to achieve a high energy density in a supercapacitor has been a long‐standing challenge. Here, graphite is reported as a high‐energy alternative to the frequently used activated carbon (AC) cathode for supercapacitor application due to its unique Faradaic pseudocapacitive anion intercalation behavior. The graphite cathode manifests both higher gravimetric and volumetric energy density (498 Wh kg −1 and 431.2 Wh l −1 ) than an AC cathode (234 Wh kg −1 and 83.5 Wh l −1 ) with peak power densities of 43.6 kW kg −1 and 37.75 kW l −1 . A new type of Li‐ion pseudocapacitor (LIpC) is thus proposed and demonstrated with graphite as cathode and prelithiated graphite or Li4 Ti5 O12 (LTO) as anode. The resultant graphite–graphite LIpCs deliver high energy densities of 167–233 Wh kg −1 at power densities of 0.22–21.0 kW kg −1 (based on active mass in both electrodes), much higher than 20–146 Wh kg −1 of AC‐derived Li‐ion capacitors and 23–67 Wh kg −1 of state‐of‐the‐art metal oxide pseudocapacitors. Excellent rate capability and cycling stability are further demonstrated for LTO‐graphite LIpCs. Abstract : A graphite cathode stores charge via a Faradaic pseudocapacitive intercalation process, which is distinct from the surface electrostatic adsorption of activated carbon (AC). A higher energy density can be achieved on a graphite cathode than an AC cathode, while maintaining excellent power capability. Li‐ion pseudocapacitors based on graphite cathode are proposed and demonstrated.